Bioactivity of Fe2O3-CaO-SiO2 glass ceramics modified through the addition of P2O5 and TiO2. Issue 9 (15th June 2017) - Wang, Y.Y.; Li, B.; Luo, W.Q.; Cao, F.
Abstract: The bioactivity of ferromagnetic glass ceramics is one key factor affecting the success of hyperthermia treatments. In order to investigate the effect of the addition of a nucleating agent on the bioactivity of the resulting glass ceramics, two different nucleating agents were used for the fabrication of Fe2 O3 -CaO-SiO2 glass ceramics, and their short-term and long-term effects on the cytotoxicity of human fetal normal colonic mucosa cells were evaluated. The results show that P2 O5 promotes the formation of an apatite-like phase on the surface of Fe2 O3 -CaO-SiO2 glass ceramics immersed in simulated body fluid. While TiO2 had some adverse effect on the cell viability, P2 O5 had little effect on the cell viability over a certain concentration range. In this paper, the prepared Fe2 O3 -CaO-SiO2 glass ceramics with P2 O5 added as nucleating agent are demonstrated to exhibit a good bioactivity and low cytotoxicity, which suggests good application prospects in the field of hyperthermia.